Detection of High Radar Reflectivity Volumes at High Tropospheric Levels in Large Hail Events - Tomeu Rigo; Carme Farnell (Atmosphere)
Different giant and very large hail events have occurred in Catalonia (NE of the Iberian Peninsula) in the last three years, with stones ranging between 8 and more than 10 cm in diameter. These sizes have not occurred in this area in at least thirty years. This research analyzed all those events with at least one severe hail register (more than 2 cm diameter) in the region for 2013–2023. The present study considered large volumes of high reflectivity in weather radar 3D fields at high tropospheric levels (more than 10 km). The goal was to determine if high reflectivity cores (over 55 dBZ) occurred at those levels before or during the hail-fall. The main question was whether this radar signature could reveal the occurrence of very large or giant hail. The 55 dBZ volumes occurred and were maintained over 10 km between six and sixty minutes in a high percentage of large-hail cases. However, giant hail cases did not present the maximum duration of high reflectivity at high levels as was initially expected.